Radiation-induced apoptosis varies among individuals and is modified by sex and age. (October 2014) - Applebaum, Mark A.; Skol, Andrew D.; Bond, Elisabeth E.; Overholtzer, Michael; Bond, Gareth L.; Onel, Kenan
Abstract Purpose: Although there are considerable data on mechanisms of radiation-induced apoptosis in vitro and in animal models, little is known about functional variation in these pathways in humans. We sought to develop a tractable system to evaluate this. Materials and methods: Peripheral blood mononuclear cells were isolated from 90 healthy volunteers, divided into two aliquots, one irradiated with a 5 Gy dose and the other sham-treated (0 Gy), and assessed for damage-induced apoptosis after 24 hours. To investigate reproducibility, 10 individuals spanning the entire radiation-induced apoptotic range were tested three times each, with 3–6 months between replicates. Results: We observed surprising heterogeneity in apoptosis among individuals, ranging from 21–62%. Biological replicates from a single individual, however, were completely concordant, suggesting the variability observed across individuals is not the result of stochastic or short-term effects. We found significantly higher radiation-induced apoptosis in males than in females (Mean: 41.0% vs. 30.7%; p < 3.5 × 10−7). Moreover, advancing age was associated with decreasing radiation-induced apoptosis in males (p = 0.01) but not females (p = 0.82). Conclusions: Our results provide evidence that the function of cellular pathways crucial for stress-induced apoptosis varies by sex and could decline with age in humans.